1987
DOI: 10.1007/bf02470582
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal bleeding attributed to ruptured periumbilical varices. A case report and a review of the literature

Abstract: A 50 year old man, who had had liver cirrhosis of 10 years, without previous variceal bleeding, presented with sudden abdominal pain, distension and hypotension and was admitted. The diagnosis of ruptured periumbilical varices was established at laparotomy. Despite surgical intervention to halt the bleeding varices the patient died of hepatic failure fourteen days postoperatively. The differential diagnosis and management of hemoperitoneum in this cirrhotic patient are discussed, and sixteen previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Chawla et al reported the presence of gallbladder varices in patients with extrahepatic venous obstruction. Occurrence of hemoperitoneum in patients with cirrhosis due to rupture of varices (namely, collaterals of the veins of Retzius connecting the superior and inferior mesenteric veins with the lumbar and the lower intercostals veins), venous collaterals connecting the liver with the diaphragm (Sappey veins), and recanalized paraumbilical collaterals draining left portal vein to epigastric veins of the anterior abdominal wall (Cruveillier‐Baumgarten syndrome) have been described. Familial cases of ectopic varices have also been reported .…”
Section: Etiology and Prevalence Of Ectopic Varicesmentioning
confidence: 99%
“…Chawla et al reported the presence of gallbladder varices in patients with extrahepatic venous obstruction. Occurrence of hemoperitoneum in patients with cirrhosis due to rupture of varices (namely, collaterals of the veins of Retzius connecting the superior and inferior mesenteric veins with the lumbar and the lower intercostals veins), venous collaterals connecting the liver with the diaphragm (Sappey veins), and recanalized paraumbilical collaterals draining left portal vein to epigastric veins of the anterior abdominal wall (Cruveillier‐Baumgarten syndrome) have been described. Familial cases of ectopic varices have also been reported .…”
Section: Etiology and Prevalence Of Ectopic Varicesmentioning
confidence: 99%